Reconstruction of Contracted Eye Socket With Autogenic Dermal Sphere Connected to Epidermis. Issue 6 (September 2018) - Tian, Rui; Xu, Haitao; Huang, Xinyu; Wang, Xingxing; Zhang, Jialu; Du, Yuanyuan
Abstract : Background: Because of the deficiency of blood circulation and soft tissue, reconstruction of the eye socket for severe conjunctival sac stenosis in anophthalmic patients is very difficult. In this article, the authors report an innovative technique for conducting a 1-stage operation to reconstruct the contracted eye socket with an autogenic dermal sphere connected to the epidermis (ADSE). Methods: Five patients, each having a single severely contracted eye socket and conjunctival sac, were included in this study. An ADSE was transplanted into the contracted eye socket and conjunctival sac. After the operation, several observation indexes were evaluated, such as the survival and stability of implanted autologous tissue, the improvement of the contracted eye socket, and the degree of patients' satisfaction with their appearance. Results: All of the implanted epidermal and dermal tissues survived well after 6 months' observation. Although somewhat absorbed, the transplanted dermal ball was plump in the eye socket, and the epithelial tissues merged well with the residual conjunctival epithelium. Moreover, the transplanted epidermis assumed a mucosal appearance in 4 of 5 patients. After reconstruction of the eye socket, the size of the conjunctival sac and depth of the eye socket were corrected sufficiently for patients to wear an ocular prosthesis. Conclusions: The implantation of an ADSE can reconstruct a severely contracted eye socket in anophthalmic patients. Because of the high survival rate and limited absorption ratio, this 1-stage operation satisfied both patients and their ophthalmologists.